1990
DOI: 10.1007/bf02010727
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal ulcerations induced by anti-inflammatory drugs in rats

Abstract: Aspirin, diclofenac, diflunisal, ibuprofen and indomethacin were given orally or intravenously to fasted or fed rats. The resulting gastric and intestinal damage was assessed using standard methods. The same drugs were administered to rats with biliary fistulas, and the fraction of drug excreted in bile was quantified using HPLC methods. We found that gastric damage occurred only in the fasted animals and was found to be dose-dependent and related to the amount (r = 0.871) and solubility (r = 0.909) of the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 40 publications
2
72
0
Order By: Relevance
“…BFMeT induces small intestinal ulcers in rats like other NSAIDs (2,30,36). Recently, we reported that BFMeT induced ileal ulcers in specific pathogen-free rats but no ulcers in germ-free rats or gnotobiotic rats monoassociated with L. acidophilus and B. adolescentis, and that antibiotic treatment, which decreases the total number of bacteria, inhibited ulcer formation (36).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…BFMeT induces small intestinal ulcers in rats like other NSAIDs (2,30,36). Recently, we reported that BFMeT induced ileal ulcers in specific pathogen-free rats but no ulcers in germ-free rats or gnotobiotic rats monoassociated with L. acidophilus and B. adolescentis, and that antibiotic treatment, which decreases the total number of bacteria, inhibited ulcer formation (36).…”
Section: Discussionmentioning
confidence: 98%
“…When NSAIDs are administered to rats, ulcers are observed in the small intestine (2,30,36). Therefore, NSAID-induced small intestinal ulceration in rats may be a useful animal model for human ulcers.…”
mentioning
confidence: 99%
“…hepatic circulation of NSAIDs and their metabolites (2,9,29). The gastric and duodenal or ileal damage caused by NSAID toxicity are explained by different factors such as acid and pepsin or intestinal bacteria, respectively (3,26).…”
mentioning
confidence: 99%
“…Furthermore, an additional physical mechanism such as binding of the proanthocyanidins to the gastric mucosa proteins cannot be ruled out since procyanidins can bind to bovine serum albumin (Saito et al., 1998). On the other hand, indomethacin-induced ulcers seemed to involve inhibition of gastric prostaglandins derived mainly via COX-1, with some involvement of COX-2 (El-Bayer et al, 1985;Beck et al, 1990;Iseki, 1995;Wallace, 1997;Schmassmann et al, 1998). Stress-induced ulcers are believed to result from an increase in gastric acid secretion (Kitagawa et al, 1979;Marrone, 1984), a decrease in gastric PGE 2 production (Moody, 1976;Arakawa et al, 1981) and disturbed microcirculation in the gastric mucosa (Murakami et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Stress-indomethacin ulcers were induced in male Wistar rats by a modification of the methods described by Senay and Levine (1967), Levine (1971), Bhargava et al (1975), Beck et al (1990) and Schmassmann et al (1998). In brief, all animals were fasted for 48 h from food only with the respective drinking liquids ad libitum.…”
Section: Induction Of Stress-indomethacin Ulcersmentioning
confidence: 99%